2020
DOI: 10.1039/d0sc04390g
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalysed tetradehydro-Diels–Alder reactions of enediynes via a rhodium-stabilized cyclic allene

Abstract: Efficient methods for the synthesis of fused-aromatic rings is a critical endeavour in the creation of new pharmaceuticals and materials. A direct method for preparing these systems is the tetradehydro-Diels–Alder...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This analysis also indicated that the formation of a mixture of the allene/propargylic borylated products observed 37a , 37b , and 37c , which were isolated as a mixture in 95% yield. The formation of these products suggested that the mechanism of the reaction was similar to previously reported reactions using a rhodium precatalyst and ( Z )-enediynes . It is hypothesized that 37a – c arise from the HBpin-initiated hydroborylation of the intermediate nickellacycle represented by two resonance contributors: a propargyl Ni intermediate 36a and allenyl-Ni 36b containing a highly strained bent allenyl nickel moiety.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This analysis also indicated that the formation of a mixture of the allene/propargylic borylated products observed 37a , 37b , and 37c , which were isolated as a mixture in 95% yield. The formation of these products suggested that the mechanism of the reaction was similar to previously reported reactions using a rhodium precatalyst and ( Z )-enediynes . It is hypothesized that 37a – c arise from the HBpin-initiated hydroborylation of the intermediate nickellacycle represented by two resonance contributors: a propargyl Ni intermediate 36a and allenyl-Ni 36b containing a highly strained bent allenyl nickel moiety.…”
Section: Resultssupporting
confidence: 89%
“…The formation of these products suggested that the mechanism of the reaction was similar to previously reported reactions using a rhodium precatalyst and (Z)-enediynes. 14 It is hypothesized that 37a−c arise from the HBpin-initiated hydroborylation of the intermediate nickellacycle represented by two resonance contributors: a propargyl Ni intermediate 36a and allenyl-Ni 36b containing a highly strained bent allenyl nickel moiety. 1 H and 13 C NMR spectroscopic analysis indicated a complex mixture of isomeric products; the propargylic vinyl boronate 37a as well as two allenic vinyl boronates 37b and 37c.…”
Section: The Journal Of Organic Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of these ene-diynes 124 with 2.5 mol% of the basic trigold oxo complex [(Ph 3 PAu) 3 O]BF 4 gave the isoindolinones 125 via a novel cycloaromatization process that involved a dual goldcatalyzed reaction pathway (Scheme 33b). [77] Other collaborative efforts have also uncovered a novel Rh I -catalyzed dehydro Diels-Alder reaction of enediynes 126 proceeding O via a rhodium-stabilized cyclic allene (Scheme 33c) [78] and the Pd-catalyzed asymmetric allylic alkylation reactions of sulfamidate imines. [79] In other studies on metal-promoted or metal-catalyzed cyclization reactions we have reported cyclization-cyanation and cyclization-halogenation reactions of β-hydroxyalkynes and o-alkynyl-anilines and phenols, leading to valuable 3-cyano-indoles and benzofurans, [80] and cycloisomerization reactions leading to furo[3,2-b]pyridines and furo [3,2-b]pyrroles.…”
Section: Other Developments On the Pbmrmentioning
confidence: 99%
“…Diels–Alder reactions are atom-efficient protocols for the construction of novel six-membered carbon-ring or heterocycle systems from acyclic precursors. Besides the classical Diels–Alder reaction, there exists a particular category, the tetradehydro-Diels–Alder (TDDA) reaction 3 , involving enynes and alkynes, which results in a high-energy cyclic allene 4 intermediate that undergoes a [1,5] H shift to generate a stable benzene/arene ring (Scheme 1a). Although the thermal TDDA reaction 5 was demonstrated to be a valuable tool for functional aromatic rings, constrained reaction conditions and substrate scope limited its synthetic applications.…”
mentioning
confidence: 99%